(untitled) (Biological Sciences - PJSIR, 1996)
Three nematicides viz. rugby, furadan and tenekil-M were tested for comparison against plant parasitic nema- todes i. e. Helicotylenchus indicus, Hoplolaimus indicus, Longidorus elongatus Pratylenchus brachyurus and Rotylenchulus renifomis are attacking cotton. After 16weeks of the experiment the number of plant parasitic nema- todes recovered from rugby were 42, furadan 153,tenekil-M 165and control 525 per 100m1of the soil the average yield of cotton was 370 g in rugby, 252 g in furadan, 370g in tenekil-M and 245 g in control.